Captive power, market access, and welfare effects in the Bangladesh electricity sector - Sakib Amin; Tooraj Jamasb; Manuel Llorca; Laura Marsiliani; Thomas I. Renström (Copenhagen Business School (CBS), Department of Economics, 2020)
Electricity sectors in many emerging and developing countries are characterised by significant captive industrial generation capacity. This is mainly due to unreliable electricity supplies from state-owned utilities. Integrating the captive capacity with the on-grid supply can improve resource utilisation in the electricity market. We use a Dynamic Stochastic General Equilibrium (DSGE) model to examine the effects of allowing the Bangladeshi Captive Power Plants (CPPs) to sell their excess output to the national grid at regulated prices. We find that opening the grid to CPPs would reduce the industrial output and GDP due to energy price distortions. We also show that the Bangladeshi economy would become more vulnerable to oil price shocks when CPPs are connected to the national grid. These results support the second-best theory, which implies that granting grid access without removing other price distortions can lead to economically inefficient outcomes. We propose that the government should not open the grid to CPPs to minimise energy market distortions yet. Instead, it should first consider alternative reform measures such as taking steps to reduce price distortions and enabling a competitive market environment.
hdl:10398/9813
Keywords: D58; L94; Q43; Q48; 330; Bangladesh; CPPs; DSGE model; Electricity generation